Managerial ownership in moderating tax avoidance - Bernice, Millicent; Hutagalung, Galumbang; Sitepu, Wilsa Road Betterment; Simorangkir, Enda Noviyanti (Journal of Economics and Business Letters, 2024)
The intention of this study is to investigate the impact of debt policy, audit committees, and company size on tax avoidance and to investigate whether managerial ownership exerts a moderating influence on the relationship between these three variables. This study implemented quantitative data using a purposive sampling technique and obtained 32 observation data from eight companies between 2019 and 2022 Indonesia Stock Exchange financial statements of real estate and property enterprises. Structural equation Modelling (SEM) was used to analyze the data using the SmartPLS application. The novelty of this study is that it adds managerial ownership as a moderating variable on tax avoidance and tests the data using a regression analysis with the PLS approach. The findings of this study show that managerial ownership moderates the effect of debt policy on tax avoidance, while Debt Policy, Audit Committee, and Company Size have no effect on Tax Avoidance, and managerial ownership is unable to moderate the effect of Audit Committee and Company Size on Tax Avoidance.